1983
DOI: 10.1016/s0010-9452(83)80028-8
|View full text |Cite
|
Sign up to set email alerts
|

rCBF For Middle-Aged Males and Females During Right-Left Discrimination

Abstract: rCBF was measured in 10 male and 10 female normal righthanders with an average age of 44.2 years. For the measures f1 and IS significant occipital lobe activation was produced bilaterally and for the measure IS significant left hemisphere parietal activation was produced also by a visually presented right-left discrimination cognitive activation task over and above the activation produced by a sensorimotor control task. The amount and pattern of blood flow changes were similar for both sexes. Performance of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2

Year Published

1988
1988
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 27 publications
0
14
2
Order By: Relevance
“…Only one rather old imaging study has looked at the underlying neuro-cognitive mechanism for sex differences in left-right confusion. However, no differences between men and women were found (Hannay et al, 1983). In this study, the spatial resolution of the applied imaging method was too low to investigate detailed anatomical involvement in men and women, which might partly explain the lack of a sex difference finding in brain activation.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Only one rather old imaging study has looked at the underlying neuro-cognitive mechanism for sex differences in left-right confusion. However, no differences between men and women were found (Hannay et al, 1983). In this study, the spatial resolution of the applied imaging method was too low to investigate detailed anatomical involvement in men and women, which might partly explain the lack of a sex difference finding in brain activation.…”
Section: Introductionmentioning
confidence: 69%
“…The few neuroimaging studies on LRD conducted on healthy participants mostly confirm the findings from previous lesion studies. Two rather old imaging studies found bilateral occipital (Hannay et al, 1983;Leli et al, 1982), as well as bilateral parietal (Leli et al, 1982), and the left parietal (Hannay et al, 1983) increase in blood flow during LRD. The particular involvement of the left hemisphere is further supported by a more recent transcranial magnetic stimulation (TMS) study , which showed that repetitive TMS (1 Hz) over the left angular gyrus disrupts LRD, as compared to TMS over the right angular gyrus.…”
Section: Introductionmentioning
confidence: 94%
“…While some studies reported no gender differences in CBF (Melamed et al, 1980;Hannay et al, 1983), others found that women had higher rates of CBF than men and that was related to age, since by the sixth decade (Gur et al, 1987) men and women had similar flow rates. PET (Rodriguez et al, 1988;Gur and Gur, 1990;Jaeger et al, 1998;Ragland et al, 2000) and fMRI (Kastrup et al, 1999) studies found differences in activation during resting state (Rodriguez et al, 1988), cognitive tasks (Gur and Gur, 1990;Jaeger et al, 1998;Ragland et al, 2000), or visual stimulation (Kastrup et al, 1999).…”
Section: Gender Differences In Activationmentioning
confidence: 95%
“…The absence of a similar asymmetrical pattern in women is, how ever, pUzzling. It may indicate true sex differences in the organization of the cerebral cortex (Hannay et al, 1983;Warkentin et al, 1986) but may also reflect sex-related differences in the functional state of the brain during the examination period, e.g., more verbal activity in resting women.…”
Section: Asymmetriesmentioning
confidence: 99%